Iron Will [videorecording (DVD)] - Haid, Charles, 1943-; Astin, Mackenzie, 1973-; Spacey, Kevin; Stiers, David Ogden; Cox, Brian, 1946- (Buena Vista Home Entertainment, 2002)
Based on an incredible true-life story. A brave young man is thrust into adulthood as he and his courageous team of sled dogs embark on a grueling and treacherous cross-country marathon. Together they race through the frozen wilderness carrying hopes of capturing the $10,000 grand prize that will save his family from financial ruin. With dogged determination and sheer iron will, they face impossible odds and hardships along the dangerous trail to his dreams.